Respons Pertumbuhan Amaranthus tricolor L. Varietas Early Splendor dari Beberapa Variasi Media Tanam - Dwi Gusmalawati (Universitas Islam Raden Rahmat, Malang, 2023)
Amaranthus tricolor L. variety Early Splendor known as red spinach is a plant with striking pink leaves that is used as an ornamental plant. This spinach has a high nutritional content, so cultivation needs to be carried out. The purpose of this study was to determine the growth response of the red spinach variety Early Splendor from several media variations. A completely randomized design with three treatments, namely variations in growing media (soil + burnt litter, soil + burnt husk, and soil + cocopeat) was used in this study. Each treatment included three repetitions. The various growing media had no significant effect on growth speed and maximum growth potential but had a significant effect on plant height, number, and length of leaves. The best planting media in producing the growth of red spinach plants of the Early Splendor variety were soil + burnt litter and soil + burnt husk, while the soil + cocopeat media produced the lowest growth.